SERAPAN FOSFOR, PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS KEDELAI (Glycine max L. Merril) YANG DIBERI PUPUK FOSFOR - Rhoma Istikhori; Aslim Rasyad; Wardati ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The soybean plants need a phosphorus in a great quantity for growth and production. Phosporus is one of essential nutrients for plants, but its availability in soil is tended to decrease. Therefore, the effective step to increase soybean production is using the soybean varieties with high productivity that can survive in the poor soil of nutrients P. This study aimed to examine the effect of fertilizer P to P uptake, growth and soybean varieties production. The eksperiment was conducted in an experiment station of Faculty of Agriculture, University of Riau lasted for 6 month started on April 2013 to August 2013. Four soybean varieties are Anjasmoro, Grobogan, Argomulyo and Burangrang planted with three level of dosage of fertilizers, there are 0 kg P2O5/ha, 25 kg P2O5/ha, 50 kg P2O5/ha. The parameter of observation include the phosphorus uptake, height plant, days of flowering, days of harvesting, weight of 100 seeds, number of seed per plant and result per m2. This study result indicate that the best P uptake are Anjasmoro and Argomulyo on 25 kg/ha fertilizer P but Grobogan and Burangrang on fertilizer P as much as 50 kg/ha. Giving the fertilizer P can increasing the growth and production on a certain varieties, while another varieties can’t showed the effect of giving fertilizer. Keywords : soybean varieties, fertilizer P, nutrients, component result